Syriac and Hebrew Words in the Dialect of Southern Iraq (Thi Qar Specifically) - Amal Adee Polus; Adnan Shibeeb Jasim (Zanco Journal of Humanity Sciences)
This research deals with Syriac and Hebrew vocabulary in the southern Iraqi dialect, Thi Qar region specifically, and it studies this vocabulary in terms of semantic and meaning. This vocabulary is considered originality even though they are not Arabic, but it derives its originality from the original people who speak it. In fact, many vocabularies continue in the dialect because it is from people’s original languages, and Iraqis have preserved them and still use and speak it to this day. The persistence of this vocabulary is due to the fact that the speaker did not find a suitable alternative for them in terms of meaning, or that they are linked to popular heritage (folklore) or the Iraqi personality, or that they are names of things that are frequently used.